Strategi Refleksi: Solusi Integratif Berpikir Analisis dan Komunikasi Ilmiah Siswa SMAN 1 Campalagian dalam Pembelajaran Fisika - Nurbayatia Nurbayatia; Firdaus Daud; Muhammad Arsyad (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to investigate the effect of applying reflective methods on students' scientific communication skills and analytical thinking abilities at SMAN 1 Campalagian in the context of physics teaching. The approach used is quantitative with a quasi-experimental design, and the design applied is a Pretest-Posttest Control Group. The sample in this study consists of two groups: the experimental group using the reflective method and the control group following conventional learning methods. Data on scientific communication skills were collected through observation sheets, while analytical thinking abilities were measured with essay tests. Data analysis was conducted using descriptive and inferential statistics through an independent sample t-test. The results show that the average scientific communication ability of students in the experimental group reached 71.21, which is higher compared to the control group, which scored 68.82. with a difference of 2.39 points. On the other hand, the average analytical thinking ability of students in the experimental group was 73.11, while the control group scored 60.12, with a difference of 12.99 points. The hypothesis test showed a significance value of 0.001 (< 0.05) for both variables. Thus, it can be concluded that applying the reflection method has a positive and significant impact on students' scientific communication skills as well as their analytical thinking skills in learning physics.